The Investigasi Pengetahuan Kesiapsiagaan Bencana Pada Mahasiswa ditinjau dari Perbedaan Gender - Rima Meilita Sari; Ridhwan Ridhwan (Universitas Prof. Dr. Hazairin, S.H, 2019)
Disasters in Aceh are not limited to the earthquake and tsunami disaster that occurred in 2004. To form a disaster-response community, efforts are needed to shape disaster knowledge. The purpose of this knowledge are 1) knowing the level of knowledge of students' disaster, 2) knowing the level of knowledge of students' disasters in terms of gender, and 3) knowing the effect of gender on students' knowledge of disaster preparedness. The research uses quantitative methods by involving geography education students at STKIP Alwashliyah. Data were analyzed using the ANCOVA test method and descriptive statistics. The results show 1) the level of knowledge of student disaster preparedness is in the low category, 2) student disaster preparedness is also in the low category when viewed from gender differences, and 3) there is an influence of gender on knowledge of disaster preparedness. Based on the research findings, efforts are needed to increase disaster preparedness knowledge by incorporating disaster curriculum into geographic subjects, developing methods and learning media that can help the implementation of disaster learning and routinely conduct training so that disaster preparedness can be realized. Keywords: Knowledge, Disaster Preparedness, Students, Gender